Motivational factors that influence in the english language learning with the students at “Técnico Agropecuario Gonzanamá” high school. Academic year 2012-2013 - Camacho Camacho, Angélica María (2015)
The present research work entitled: “MOTIVATIONAL FACTORS THAT INFLUENCE IN THE ENGLISH LANGUAGE LEARNING WITH THE STUDENTS AT “TECNICO AGROPECUARIO GONZANAMA” HIGH SCHOOL. ACADEMIC YEAR 2012-2013”, has been developed with the purpose of determining the influence of motivational factors in the English language learning. The scientific, descriptive, analytic-synthetic and explicative methods were used to develop every part of this research. A survey was applied to teachers and students to verify the hypotheses through the logical analysis of the results and the descriptive statistics was used to represent the data in tables and graphs. The results indicated that teachers expect from students a natural intrinsic motivation and interest for the subject while students expect the opposite, that is to say, that teachers apply extrinsic motivational factors most of the time during the English class; Students are not aware about the usefulness, relevance and importance of learning the English language, therefore students have a low achievement in the English subject because the lack of motivation.